Retrospective comparison of semipermanent and permanent cementation of implant-supported single crowns and FDPs with regard to the incidence of survival and complications - Kappel, Stefanie; Schröder, Christin; Corcodel, Nicoleta; Hassel, Alexander J.; Rammelsberg, Peter (Clinical implant dentistry and related research, 2012)
Purpose: To retrospectively compare the fixation modalities semipermanent and permanent for all cemented single crowns and Fixed Dental Prostheses (FDPs) placed at the Department of Prosthodontics in the years 2002 to 2010 with regard to the incidence of survival and complications. Materials and Methods: Two hundred forty-one patients (48.5% male, mean age 57.3 years) received 166 FDPs and 232 single crowns. A total of 50.6% of the FDPs and 54.7% of the single crowns were fixed using semipermanent cements. Aside from fixation, age, gender, type, location, and material of the suprastructures were assessed as possible factors affecting complications, namely de-cementation, chipping, framework, or abutment fracture. Results: During an observation period of up to 6.6 years (mean 2.24 years; standard deviation 1.38), the survival rates were 96.4% and 100% for FDPs (semipermanent/permanent cementation), and 98.4% and 92.4% for single crowns (semipermanent/permanent). The success rates achieved, counting every complication, for the FDPs were 61.9% and 70.7% (semipermanent/permanent) and for single crowns were 75.6% and 77.1% (semipermanent/permanent). The cement used had a significant effect on loss of retention of the FDPs (p = .006), but no significant effect on the retention of the single crowns. Cementation procedure exhibited no significant impact on chipping for both FDPs and single crowns. The frequency of framework or abutment fractures was too low for further statistical analyses. Conclusion: Both semipermanent and permanent cementation of FDPs and single crowns resulted in high survival rates. Within the limitations of the study design, because of the amount of chairside aftercare required, implant-borne FDPs could be recommended for permanent cementation.